Understanding and Preferences of Islamic Finance Among Gen Z - Hilya Zulva; Syahnur Aida Alifia; Muhammad Misbakul Munir (Penerbit Hellow Pustaka, 2024)
This study explores the understanding and preferences of Islamic finance among Generation Z by referring to Surah Al-Kahf verse 46. Generation Z, as a growing cohort in the digital era and globalization, has an increasingly important role in global economic development. Qualitative research methods are used to gain in-depth insight into the financial perspectives and beliefs of this generation, while verse 46 of Surah Al-Kahf was chosen as the theological basis for interpreting Islamic financial values. Results showed that, despite exposure to global culture, Generation Z showed significant interest in the concepts and principles of Islamic finance, as described in Surah Al-Kahf verse 46. Their understanding of these values influences their preferences for financial products and services. The implications of these findings for the financial industry and policymakers are presented, highlighting the importance of understanding and accommodating young people's preferences in more inclusive sustainable economic development, in line with the teachings of Surah Al-Kahf verse 46. This research aims to contribute to a better understanding of how Islamic financial values, as stated in the Qur'an, can guide the transformation of the global economy towards greater sustainability and inclusiveness.